Evaluasi Kebijakan Perda No 3 Tahun 2016 Tentang Penataan dan Pemberdayaan PKL (Pedagang Kaki Lima) di Kabupaten Sidoarjo (Studi di Pasar Larangan Sidoarjo) - Elisa Dwi Rahmawati; Achluddin Ibnu Rochim; Indah Murti (Journal of Research and Development on Public Policy, 2024)
The purpose of this study is to evaluate the policies regarding the organization and empowerment of street vendors (PKL) in Pasar Larangan Sidoarjo. This research was conducted in the PD. Pasar Larangan Sidoarjo area using data collection methods such as interviews, observations, and documentation. The study employs a qualitative approach based on William N. Dunn's policy evaluation theory, which includes six indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results indicate that the policy has not been fully maximized, especially in terms of infrastructure improvements such as drainage systems and main roads, which still require attention and enhancement. However, the policy has yielded positive outcomes in several aspects, such as improved cleanliness, aesthetics, and traffic flow in Pasar Larangan. Nonetheless, to achieve optimal effectiveness, adjustments and additional measures are needed to address critical infrastructure issues and ensure that the policy fully meets its established goals.